Evolution of Early Equus in Italy, Georgia, the Indian Subcontinent, East Africa, and the Origins of African Zebras - Bernor, Raymond L.; Cirilli, Omar; Jukar, Advait M.; Potts, Richard; Buskianidze, Maia; Rook, Lorenzo (Frontiers in Ecology and Evolution, 2019)
We report here ecological and morphological characterization of the main Old World Equus in North America, Asia, Europe and Africa, by comparing the studied fossil forms with the living Equus grevyi zebra. Equus simplicidens from North America, Equus livenzovenzis, Equus stenonis and Equus stehlini from Italy, Equus sivalensis from India, Equus cf. stenonis and a small Equus from Georgia (Caucasus), Equus oldowayensis, Equus koobiforensis and Equus cf. tabeti from Kenya and the extant Equus grevyi are described in their cranial and dental features and are compared in morphological postcranial dimensions by means of log10 ratio analysis. The occurrence of the two horses at the Dmanisi Homo site in Georgia is reported here for the first time. Our comparative analyses allow to confirm the primitive lineage of the ancient zebras as derivate from Equus simplicidens, and the successive evolution of the stenonine horses in Asia, South Asia, and Europe during the Plio – Pleistocene. The morphological analysis has reveal a clear trend in third metacarpals and third metatarsals of E. simpicidens, the small Equus from Dmanisi and E. grevyi, suggesting a close relationship between these species. The trend of the stenonine Equus from Europe and Asia confirms the possible evolution from the North America Equus simplicidens. The description of all the Old World Equus is integrated with an overview of their paleoecological context, with a referred section for each locality where these fossils were found. This contribution represents a comprehensive review of the present knowledge of the Old World Equus evolutionary history, with some new important data in deciphering the deep origin and evolution of ancient and living zebras.